The divisive state of social policy : the 'Bedroom Tax', austerity and housing insecurity. - Bogue, Kelly (Bristol : Policy Press, 2019)
Few aspects of austerity politics have been as divisive as the 'Bedroom Tax'. This book provides a vivid and authoritative assessment of the impact of social housing reform on tenants and society, using personal stories from one estate to explore its connections to issues including housing insecurity, poverty and damage to social networks.
Front cover; Title Page; Copyright Page; Dedication; Table of Contents; List of terms and abbreviations; Acknowledgements; 1. Introduction: the repositioning of social housing and welfare provision; 2. Life without state-supported housing; 3. Living in a state of insecurity; 4. Social housing insecurity as policy and ideology; 5. Divisive social policy: the competition for physical and symbolic resources; 6. Community and belonging; 7. Housing precarity and advanced marginality in the UK; Appendix; Notes; References; Index; Back cover
Print version record.
Includes bibliographical references and index.
JSTOR
Keywords: Housing policy -- Great Britain; Property tax -- Great Britain; Logement -- Politique gouvernementale -- Grande-Bretagne.; Impôt sur la fortune -- Grande-Bretagne.; POLITICAL SCIENCE / Public Policy / Social Policy; Housing policy; Property tax; Great Britain; Electronic books; Electronic book